Identification of instruments for evaluation of behavioural and psychological parameters associated with obesity management: A systematic review with narrative synthesis of the findings. Issue 1 (January 2022) - Chopra, Sakshi; Ranjan, Piyush; Malhotra, Anita; Sarkar, Siddharth; Kumari, Archana; Kaloiya, Gauri Shankar; Dwivedi, S.N.; Siddhu, Anupa; Vikram, Naval K.
Abstract: Background and aims: To identify instruments used to evaluate the predictors of successful weight loss across weight loss trials. Methods: We searched PubMed, PsychInfo, Cochrane Reviews and Scopus for weight loss trials reporting instruments published in the last 16 years. Results: A total of 46 significant behavioral and psychological predictors were identified, of which 32 instruments were finally selected. SF-36 questionnaire and Obesity Related Problem Scale for psychosocial health, TREMORE scale for motivation, Social Support Scale for support, Weight Efficacy Lifestyle Scale for self-efficacy and Body Shape Questionnaire for body image had moderate quality. Barriers to healthy eating questionnaire scale and Dutch Eating Behavior also had moderate quality. Conclusion: Use of uniform instruments with optimum quality can benefit clinical and community-based researchers to generate reliable datasets. Highlights: Twenty two questionnaires assessed different psychological predictors of weight loss. TREMORE was mostly used to assess motivation and readiness to initiate weight loss. Three Factor Eating Behavior Questionnaire was commonly used to assess eating behavior. Twenty-four-hour recall was uniformly used to assess dietary intake patterns. Across literature, low-quality recall methods were used to assess physical activity.